2022
DOI: 10.3389/fpls.2021.782960
|View full text |Cite
|
Sign up to set email alerts
|

Novel Mutant Alleles Reveal a Role of the Extra-Large G Protein in Rice Grain Filling, Panicle Architecture, Plant Growth, and Disease Resistance

Abstract: Plant growth and grain filling are the key agronomical traits for grain weight and yield of rice. The continuous improvement in rice yield is required for a future sustainable global economy and food security. The heterotrimeric G protein complex containing a canonical α subunit (RGA1) couples extracellular signals perceived by receptors to modulate cell function including plant development and grain weight. We hypothesized that, besides RGA1, three atypical, extra-large GTP-binding protein (XLG) subunits also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 39 publications
0
11
1
Order By: Relevance
“…This vector system resulted in nearly 90% transformation efficiency for single gene editing in rice. Earlier, we successfully generated triple edited Osxlg mutants using this vector system ( Biswal et al., 2022 ). The duplex guide oligo was inserted into the BsaI site of pRGEB32 using InFusion ® cloning at GenScript Biotech Inc., USA ( Figure 1C ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This vector system resulted in nearly 90% transformation efficiency for single gene editing in rice. Earlier, we successfully generated triple edited Osxlg mutants using this vector system ( Biswal et al., 2022 ). The duplex guide oligo was inserted into the BsaI site of pRGEB32 using InFusion ® cloning at GenScript Biotech Inc., USA ( Figure 1C ).…”
Section: Methodsmentioning
confidence: 99%
“…Target sequences were amplified by Phusion DNA polymerase (New England Biolabls, United States) using gene-specific primers flanking the target site ( Supplementary Table S3 ) using the protocol mentioned by Biswal et al. (2022) .…”
Section: Methodsmentioning
confidence: 99%
“…Cas9 has commonly been used in studies to evaluate allergens and immune-related diseases such as egg allergies [147], or to remove allergens from products such as soybean through site-directed mutagenesis [148] or target genes involved in allergic rhinitis [149]; or remove and functionally evaluate other allergens [150][151][152][153][154][155], with no literature studies having implicated Cas9 proteins themselves in allergenicity. Importantly, Nakajima et al [156] reported that Cas9 was subject to rapid digestion in vitro and unlikely to cause food allergy in the case of accidental ingestion.…”
Section: Literature Assessment Of Hcas9 Allergenicitymentioning
confidence: 99%
“…GS regulation in rice is extremely diverse with involvement of genes controlling hormones [ 15 ], G-protein signaling [ 16 18 ], ubiquitin proteasome pathway [ 19 , 20 ], and starch metabolism [ 21 ]. They can also be transcriptional activators [ 11 ], microtubule-associated proteins [ 22 ], chromatin and histone modifiers [ 23 ], or sucrose transporters [ 24 ].…”
Section: Introductionmentioning
confidence: 99%